PAIN - Novel targets and new technologies - Peter John Cabot (Frontiers Research Topics, 2015)
The problem of clinical pain management is complex and far-reaching, as it encompasses many different types of pain, such as arthritis, musculoskeletal conditions, neuropathic pain, and visceral pain. It is widely known that many of the well-established analgesic pathways are centrally based, involving spinal and supraspinal sites. However, pain can also be effectively controlled by peripheral pathways. The analgesics market is growing and the driving forces are the aging population and need for better therapeutic benefits. There are various analgesic products that are available that can be administered by various routes, yet research is active in identifying new technologies for better drug targeting and novel targets to gain improved therapeutic efficiency. This e-Book "PAIN - Novel targets and new technologies" has brought together experts in the field of pain at the physiological, pharmacological and pharmaceutical levels to discuss novel pain targets and new pain technologies across the various types of pain. This information is presented as novel research findings, short communications and review articles. The goal of this e-Book is to generate further collaborative discussion on the future and direction of pain therapies.